Condenações por síndrome ascítica em frangos abatidos sob inspeção federal entre 2002 e 2006 no estado do Rio Grande do Sul e sua repercussão econômica - Jacobsen, Gislaine (2007)
The incidence of ascites in slaughterhouses inspected by the Brazilian Agricultural Authority resulted in the condemnation of 1,605,439 broiler carcasses in the state of Rio Grande do Sul between 2002 and 2006. This figure corresponds to 8.19% of the number of total carcass condemnations in the period according to data of the Brazilian Department of Agriculture. This study aimed to discuss the causes and mechanism of control of ascites and assess the evolution of this metabolic disorder, which accounted for 6.4% of total carcass condemnations in 2002, a figure that rose to 9.6% in 2006. Linear regression showed a strong correlation (0.92), demonstrating that ascites-related condemnations are increasing. The financial losses resulting from these condemnations in that period amount to R$ 3,6 milion or US$1,7 milion , which highlights the importance of implementing more effective control and monitoring of this condition in the poultry sector.